2006
DOI: 10.3892/or.15.1.113
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of proliferative and invasive capacities of breast cancer cells by arginine-glycine-aspartic acid peptide in vitro

Abstract: Abstract. The Arg-Gly-Asp (RGD) sequence was selected by using phage-display peptides to target tumors, focusing on targeting ·(v) integrins in tumor blood vessels. Recent studies suggest that peptides containing the RGD sequence can bind to tumor cells, as well as tumor endothelial cells. To investigate whether the RGD peptide has other effects on tumor cells expressing ·(v) integrins, besides its tumor targeting capability, we designed and synthesized a 10-amino peptide that contained the RGD sequence in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
8
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 17 publications
(17 reference statements)
2
8
1
Order By: Relevance
“…4). These results are in accordance with the observations by Ma and coworkers that RGD peptide inhibited cancer cell cycle proliferation by arresting cells at G1 phase [40]. Whereas, our findings differ somewhat from those reported by Dia et al, who found that lunasin, a RGD cancer preventive peptide, induced apoptosis in human colon cancer cells by arresting cell cycle at G2/M phase [41].…”
Section: Flow Cytometry Studiessupporting
confidence: 77%
“…4). These results are in accordance with the observations by Ma and coworkers that RGD peptide inhibited cancer cell cycle proliferation by arresting cells at G1 phase [40]. Whereas, our findings differ somewhat from those reported by Dia et al, who found that lunasin, a RGD cancer preventive peptide, induced apoptosis in human colon cancer cells by arresting cell cycle at G2/M phase [41].…”
Section: Flow Cytometry Studiessupporting
confidence: 77%
“…Our results demonstrated that disulfide-based cyclization may provide an efficient approach for studying receptor binding affinity and selectivity of RGD peptides as well as enzymatic and metabolic stability of RGD peptides employed for integrin targeting 1, 45, 46. As described above, we have successfully synthesized the near-infrared fluorescent disulfide cyclic RGD peptide and evaluated their integrin α v β 3 binding.…”
mentioning
confidence: 61%
“…For applications in patients, it is important to consider the toxicity of a new compound. Because other RGD peptides were found to be cytotoxic by themselves (37), toxicity has to be investigated for HBP-1, too.…”
Section: Discussionmentioning
confidence: 99%